Environmental patterns and daily activity of dung beetles (Coleoptera: Scarabaeidae) in the Atlantic Rainforest of Brazil - Iannuzzi, Luciana; Portela Salomão, Renato; Correia Costa, Fábio; Nunes Liberal, Carolina (ENTOMOTROPICA, 2016)
The aim of the present study was to evaluate the daily activity and habitat associations of dung beetles, to examine their seasonal variation and to determine which species are dominant in a region of Brazilian Atlantic Forest. Sampling was performed with pitfall traps baited with carrion and human excrement. Dung beetles were more abundant in open habitat during the day, and in closed habitat at dusk. No difference was found in the abundance and period of activity between seasons. Species richness varied with seasonality in different habitats. Greatest species richness was found at dusk. No significant association was found between body size and period of activity. Segregation of the dung beetle community was found to be associated with the period of activity.